2014
DOI: 10.1080/00397911.2013.862833
|View full text |Cite
|
Sign up to set email alerts
|

FeCl3-Catalyzed Cascade Reaction: An Efficient Approach to Functionalized Coumarin Derivatives

Abstract: An efficient and environmentally benign synthesis of 3-substituted or 3,4-disubstituted coumarins was accomplished via iron(III) chloride-catalyzed cascade reactions of salicylaldehydes and activated methylene compounds. The reaction preceded cleanly under mild reaction conditions to provide the desired coumarin derivatives in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…Under ultrasonic irradiation, Sripathi and Logeewari [32] reported the synthesis of 3‐phenylcoumarins from salicylaldehydes and phenylacetyl chloride using K 2 CO 3 in THF, Scheme 5.…”
Section: Coumarin Synthesismentioning
confidence: 99%
“…Under ultrasonic irradiation, Sripathi and Logeewari [32] reported the synthesis of 3‐phenylcoumarins from salicylaldehydes and phenylacetyl chloride using K 2 CO 3 in THF, Scheme 5.…”
Section: Coumarin Synthesismentioning
confidence: 99%
“…Yields obtained with ethyl 2-cyanoacetate were higher than with malonoitrile. Synthesis of 3-substituted coumarins catalyzed by iron(III) chloride was reported by He et al [34]. Model reaction of salicylaldehydes and malononitrile was performed in order to determine the best reaction conditions.…”
Section: Scheme 15 Synthesis Of Coumarin-3-carboxylic Esters In Multmentioning
confidence: 99%
“…Most of the extracted coumarins have biological activity and therefore coumarin derivatives are increasingly being synthesized, since their extraction from plants is time-consuming and unprofitable (too many operation steps to the final product) [32]. Coumarins could be synthesized with many different methods like Perkin reaction, Knoevenagel condensation, Pechmann condensation, Wittig reaction, Baylis-Hillman reaction, Claisen rearrangement and Vilsmeier-Haack and Suzuki cross-coupling reaction [33,34]. Many authors have published researches exploring the medicinal properties of coumarins [4,6,12,[35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…[ 31–33 ] Most of these reactions are multistep and time‐consuming, but this has been solved by the introduction of metal‐catalyzed intermolecular or intramolecular coupling reactions. Owing to the great importance of this small, but useful, moiety, much attention has been given to the development of synthetic methods for substituted coumarins using transition‐metal catalysts such as palladium, [ 34 ] iron, [ 35 ] gold, [ 36 ] silver, [ 37 ] copper, [ 38 ] platinum, [ 39 ] nickel, [ 40 ] cobalt, [ 41 ] rhodium, [ 42 ] gallium, [ 43 ] and zinc. [ 44 ] Recently, a review based on the efficient synthetic methods for 4‐arylcoumarins has been reported.…”
Section: Introductionmentioning
confidence: 99%